Troublesome trucks: thomas & friends - Awdry, W. (Egmont London, 2008)
In "Troublesome Trucks," Thomas the Tank Engine encounters a group of mischievous trucks on the Mainland. These trucks are known for their playful pranks and love to cause trouble for the engines. Thomas, eager to prove himself, initially underestimates the trucks' antics. However, he soon learns a valuable lesson about patience, teamwork, and the importance of staying calm under pressure. With the help of his friends and a bit of ingenuity, Thomas manages to outsmart the troublesome trucks and restore order to the railway.